Pengaruh Anggaran Pendidikan, Anggaran Kesehatan, dan PDRB terhadap Indeks Pembangunan Manusia di Provinsi Jawa Tengah Tahun 2015 - 2019 - Muhammad Naufal Alif; Nugroho SBM (Universitas Diponegoro, 2021)
This study aims to determine the effect of the education budget, health budget, and GRDP on the Human Development Index in Central Java province in 2015 - 2019. The dependent variable used in this study is the Human Development Index in Central Java Province 2015 - 2019. The independent variable used in this study is the education budget, health budget, and GRDP. This study uses panel data which is a combination of time series data and cross-section data with secondary data obtained from reports published by BPS and the Ministry of Finance of the Republic of Indonesia. The analysis model used in this research is a log model that is completed with the help of Eviews 11. To see the effect of the independent variable on the dependent variable, the best estimation model is selected from the three types of models and the best estimation model is the fixed effect model (FEM). Partially, the education budget variable has a negative and not significant effect on the Human Development Index. The health budget variable has a positive but not significant effect on the Human Development Index. The GRDP variable has a positive and significant effect on the Human Development Index. The results showed that the education budget, health budget, and GRDP simultaneously had a significant effect on the Human Development Index in Central Java Province in 2015 – 2019.